THE CHOICE OF EFFECTIVE TYPES OF VIRTUAL ORGANIZATIONS FOR THE AEROSPACE INDUSTRY - O. Afanasieva; A. Kovalev (Вестник университета)
Methodological postulates that allow to raise the issue of the formation of virtual organizations in the aerospace industry in the context of corporate structures and material, mainly assets - are formulated. The classication scheme of basic virtual organizations, based on the analysis of conceptual directions of information integration, has been claried. The author’s version of the hierarchical classication scheme of virtual organizations is considered. The recommendations on the forms of virtual organizations based on the selection of the most appropriate aerospace industry from the presented classication scheme of virtualization forms are formulated.